STRATEGIC HRM IN THE AGE OF POLYCRISIS: BUILDING ORGANIZATIONAL RESILIENCE THROUGH DYNAMIC CAPABILITY DEVELOPMENT - Fitriana; Ramon Zamora; Oktavianti (International Journal of Social Science, Educational, Economics, Agriculture Research and Technology (IJSET), 2026)
This study examines the role of Strategic Human Resource Management (SHRM) in building organizational resilience in the context of polycrisis, characterized by interconnected economic, geopolitical, environmental, and technological disruptions. Drawing on a narrative literature review, the research integrates SHRM with dynamic capability theory to develop a conceptual framework linking human resource practices, sensing, seizing, and transforming capabilities, and resilience outcomes. The findings suggest that SHRM plays a pivotal role in fostering adaptability by enhancing employee engagement, skills, and organizational flexibility. HR practices such as continuous learning, leadership development, and flexible work systems contribute to the development of dynamic capabilities, enabling organizations to respond effectively to uncertainty and disruption. The study highlights that resilience is achieved through the alignment of human capital strategies with changing environmental demands. It also emphasizes the importance of integrating HR systems with broader organizational processes to support continuous renewal. The research contributes to theory by connecting SHRM and dynamic capabilities within a polycrisis context and offers practical insights for building sustainable and resilient organizations.